Arsitektur Biomimikri pada Gedung Kesenian di Kabupaten Bone - Amin, Burhanuddin; Juddah, Safruddin; Harwinda, Harwinda (TIMPALAJA : Architecture Student Journals, 2024)
_ Art is an inherent part of humanity; where there are people, art exists. An Arts Building is a venue that showcases various art forms and serves as a source of information, knowledge, education, and recreation in Bone Regency. As development increases, so does pollution. Therefore, it is essential to design buildings that can mitigate or minimize this pollution while functioning effectively, such as by creating environmentally friendly buildings. This research was conducted descriptively through a literature review, collecting information and data from books and the internet relevant to the research topic. The results show that designing an Arts Building with a biomimicry architectural approach using natural strategies is a suitable solution. One application of the biomimicry concept is the use of self-cleaning materials. The addition of TiO2 (Titanium Dioxide) to building materials aims to decompose harmful elements in the surrounding environment through a photocatalysis process similar to that in plants.